2000
DOI: 10.1002/(sici)1521-3803(20000101)44:1<38::aid-food38>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative activity of rosemary extract in lipid fraction of minced meat balls during storage in a freezer

Abstract: The influence of ethanol rosemary extract on lipid fraction of minced meat balls during storage in the freezer was studied. The quality of stored products was evaluated sensorically by the scale method and profiling of taste and aroma. Oxidative changes were investigated on the base of the changes in malonaldehyde content. It was observed that the addition of rosemary extract delayed the oxidation of lipid fraction of products. The antioxidative effect was related to the concentration of this extract in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Butler and Larick27 reported that the use of rosemary improved the sensory characteristics and oxidative stability of heat‐induced beef gels. Karpinska et al 28 found that rosemary extract decreased the rancid taste and aroma of meat dishes and the rate of undesirable changes was reduced during frozen storage. Similarly, Stoick et al 10 found a linear concentration effect of rosemary improving sensory scores of beef steaks, indicating effective antioxidant activity during frozen storage.…”
Section: Resultsmentioning
confidence: 99%
“…Butler and Larick27 reported that the use of rosemary improved the sensory characteristics and oxidative stability of heat‐induced beef gels. Karpinska et al 28 found that rosemary extract decreased the rancid taste and aroma of meat dishes and the rate of undesirable changes was reduced during frozen storage. Similarly, Stoick et al 10 found a linear concentration effect of rosemary improving sensory scores of beef steaks, indicating effective antioxidant activity during frozen storage.…”
Section: Resultsmentioning
confidence: 99%
“…Addition of rosemary extract delayed the oxidation of lipid fraction of minced meatballs during storage in the freezer. The antioxidative effect was related to the concentration of the active compounds present in the extract [20,21]. Studies showed that there are biologically active compounds in rosemary essential oil exhibiting cytotoxic, antioxidant, anti-carcinogenic and cognitionenhancing properties [4].…”
Section: Discussionmentioning
confidence: 99%
“…and the appearance of a rancid taste in the products (Lee et al 1997;Kprinska et al 2000).The present study compared the antioxidant activities of 22 selected culinary herbs and spices on lipid peroxidation in pork meat by measuring the thiobarbituric reactive substances. …”
mentioning
confidence: 96%
“…and the appearance of a rancid taste in the products (Lee et al 1997;Kprinska et al 2000). and the appearance of a rancid taste in the products (Lee et al 1997;Kprinska et al 2000).…”
mentioning
confidence: 99%